2011
DOI: 10.1111/j.1420-9101.2011.02300.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection on a measure of parasite resistance varies across ages and environmental conditions in a wild mammal

Abstract: Parasites detrimentally affect host fitness, leading to expectations of positive selection on host parasite resistance. However, as immunity is costly, host fitness may be maximized at low, but nonzero, parasite infection intensities. These hypotheses are rarely tested on natural variation in free‐living populations. We investigated selection on a measure of host parasite resistance in a naturally regulated Soay sheep population using a longitudinal data set and found negative correlations between parasite inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 85 publications
(216 reference statements)
6
93
1
Order By: Relevance
“…Indeed, Soay sheep infected by nematodes may face high mortality risks during harsh winters [65], which may even lead to population crashes [66]. Furthermore, longitudinal studies on the same population found age-related changes in parasite resistance [67], [68]. These findings potentially indicate that endoparasite infections may involve higher costs in Soay sheep than in S. bilineata , especially when resources are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Soay sheep infected by nematodes may face high mortality risks during harsh winters [65], which may even lead to population crashes [66]. Furthermore, longitudinal studies on the same population found age-related changes in parasite resistance [67], [68]. These findings potentially indicate that endoparasite infections may involve higher costs in Soay sheep than in S. bilineata , especially when resources are limited.…”
Section: Discussionmentioning
confidence: 99%
“…FEC has also been shown to be negatively related to body mass at the time of sampling and to subsequent survival, especially in young animals (Hayward et al. 2011). …”
Section: Methodsmentioning
confidence: 99%
“…2011, 2014). Teladorsagia circumcincta is a highly prevalent GIN parasite of the Soay sheep (Craig et al.…”
Section: Introductionmentioning
confidence: 99%
“…Metazoan parasites are therefore likely to have been a central evolutionary force in the shaping of type 2 immune pathways. In a telling example from the unmanaged population of Soay sheep on St Kilda, parasitic nematodes especially in combination with malnutrition and severe weather, are the major determinants of failure to survive [8,12,13,14 ]. Thus, regulating energy metabolism and body temperature may be crucial to reproductive success in the face of helminth infection, providing a possible explanation for the association of type 2 immunity with these seemingly unrelated processes.…”
Section: Introductionmentioning
confidence: 95%
“…However, studying helminth infections will be a major route to enlightenment. From plants to fish, and from domesticated mammals to wild mammal populations, helminth burden is directly and negatively correlated with host fitness [8][9][10][11]. Metazoan parasites are therefore likely to have been a central evolutionary force in the shaping of type 2 immune pathways.…”
Section: Introductionmentioning
confidence: 98%